Editorial of the twentieth edition of Ambiente & Agua - An Interdisciplinary Journal of Applied Science - Batista,Getulio Teixeira (2012)
We now publishing the 20th edition with 20 articles evaluated and peer reviewed and since the first published issue, all editions were published as scheduled. We continue to practice the complete open access policy and fostering the visibility of articles. We continue to register doi of all articles and publishing the entire issue as a single archive in addition to the individual articles. This editorial shows citation metrics position of Ambiente & Agua based on Google Scholar Metrics in comparison with other journals.